2009
DOI: 10.1024/1421-0185.68.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Two Variants of the Method of Constant Stimuli for Estimating Difference Thresholds

Abstract: The two-alternative forced-choice (2AFC) and the reminder tasks are variants of the method of constant stimuli. One or the other task is usually employed for estimating the difference limen (DL) in psychophysical research. Lapid, Ulrich, and Rammsayer (2008) found that the 2AFC task yields larger DLs than the reminder task for duration discrimination judgments. The results of the present paper confirm that this discrepancy also generalizes to discrimination judgments about nontemporal, visual information (Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…Although it is usually assumed that the two tasks yield identical performance scores, we found that this assumption is not supported by experimental data (Lapid, Ulrich, & Rammsayer, 2008, 2009; Rammsayer & Ulrich, in press). In these studies, the 2AFC task consistently yielded larger DLs – in fact, the DLs were up to twice as large as the ones estimated by the reminder task.…”
Section: Reminder Vs 2afc Taskcontrasting
confidence: 84%
“…Although it is usually assumed that the two tasks yield identical performance scores, we found that this assumption is not supported by experimental data (Lapid, Ulrich, & Rammsayer, 2008, 2009; Rammsayer & Ulrich, in press). In these studies, the 2AFC task consistently yielded larger DLs – in fact, the DLs were up to twice as large as the ones estimated by the reminder task.…”
Section: Reminder Vs 2afc Taskcontrasting
confidence: 84%
“…A key feature of categorical perception is that stimuli that are from different perceptual categories (e.g., ‘normal’ and ‘not normal’) are more discriminable than stimuli from within the one perceptual category (e.g., two ‘normal’ stimuli) (Calder et al, 1996, Harnad, 1987). Relative judgments of stimulus features such as size and presentation interval have been used in previous studies investigating perceptual discrimination (Lapid et al, 2008, Lapid et al, 2009). To test whether portion size normality was perceived categorically, participants judged the relative size of two simultaneously displayed portions in Study 2.…”
Section: Introductionmentioning
confidence: 99%